Implementation of Brand Positioning in an Effort to Become a Religious Tourist Destination: A Hubbul Wathan Grand Mosque Study - Al Jauzi, M. Seneng; Wibowo, Hari Santoso; Wadud, Abdul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Islamic Center Masjid Raya Hubbul Wathan is the largest mosque and a religious tourism center in West Nusa Tenggara. This study examines the brand positioning strategy implemented by this mosque, which functions as both a grand mosque and a spiritual tourism center. This study uses a qualitative method with a case study approach. Data were collected by interview, observation, and documentation and tested by sources and techniques triangulation. The results show that this mosque, as the grand mosque, has numerous qualified national and international imams, magnificent and comprehensive congregational prayer facilities, and varied and high-quality Islamic studies as its differentiation. While in the category of religious tourism center, this mosque has the unique building architecture and Menara 99 icon as its main advantages. The results of this study can be a reference in the development of tourism mosques that are nowadays increasing in Indonesia.